Rancangan Pengarsipan Laporan Digital pada Instansi Dinas Kebudayaan Provinsi Bali Berbasis Google Site - I Putu Buda Suyasa; Karmana, Putu Dian; Yasa, I Putu Bagus Ambara; Wismana, Gusti Komang Tri (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
The Design of Digital Report Archiving at the Cultural Office of Bali Province based on Google Site aims to enhance efficiency and accessibility in document management. Leveraging the Google Site platform, this design integrates cloud-based data storage with collaborative features, facilitating the archiving and retrieval processes. Digital report documents, encompassing cultural activities and related projects, can be swiftly uploaded, organized, and accessed through a user-friendly interface. Data security is ensured through well-managed access rights. With the implementation of this design, the Cultural Office of Bali Province anticipates optimizing operational effectiveness, reducing paper usage, and fostering collaboration among team members in the management of digital reports.